Synthesis of perovskite-type lanthanum cobalt oxide powders by mechanochemical activation method - Supachai Sompech (2018)
Lanthanum cobalt oxide (LaCoO 3) powders were prepared from mixtures of LaCl 3 ·7H 2O, CoCl 2, and Na 2CO 3 by grinding, heating, and washing operations. The reagents were mixed in a molar ratio of 1:1:2.5 in a planetary ball mill and milled at 300 rpm for 2 h. The milled samples were heated at various calcination temperatures and washed with distilled water. Thermogravimetric and differential thermal analysis were used to evaluate the optimum conditions for calcination. Phase formation was determined by X-ray diffraction (XRD) while specific surface area was measured by the BET method. The average particle size distribution was determined by a particle size analyser and morphology studied by scanning electron microscopy (SEM). The TG and DTA curves of the milled samples indicated that the formation of LaCoO 3 occurred at temperatures in the range of 600°C to 800 °C. XRD patterns showed clearly the formation of the LaCoO 3 phase with perovskite-type structure at those temperatures. In addition, the results showed that the specific surface areas of the products decreased with increasing calcination temperature, while the average particle size D[4,3] increased. Furthermore, SEM micrographs demonstrated that the particles were in an agglomerated form with mean primary particle sizes in the range of 0.3-0.6 μm.